Slavic layer of toponyms for Beskaragay, Borodulikha and Shemonaikha districts of East Kazakhstan: linguistic aspect in the context of regional world outlook - Adilova, Zh.K.; Seitova, Sh.B. (Акад. Е.А. Бөкетов ат. Қарағанды ун-ті КЕАҚ баспасы, 2023)
The article discusses the toponyms related to the Beskaragay, Borodulikha, and Shemonaikha districts of the East Kazakhstan region. By considering the notions of toponymic space, system, and worldview, the authors study toponymy from linguo-regional, linguo-cognitive, and ethnolinguistic aspects. The toponymy of the given districts is touched upon as a part of the whole toponymic system of Kazakhstan, with its own specifics defined by geographical location, settlement history, and the ethnographic state of the region. The authors highlight the origin and semantic structure of the toponymes under consideration. The nominations are systematized in accordance with their etymological, derivational, and semantic features. As the article refers to toponymic studies, it draws certain conclusions on the contribution of toponymy to the development of modern humanitarian science.
Шығыс Қазақстан облысы Бесқарағай, Бородулиха және Шемонаиха аудандарының топонимикалық атауларының славяндық шығу төркіні: әлемнің аймақтық бейнесі контексіндегі тарихи-лингвистикалық аспект
Славянский пласт топонимических наименований Бескарагайского, Бородулихинского и Шемонаихинского районов Восточно-Казахстанской области: историко-лингвистический аспект в контексте региональной картины мира
Keywords: linguistic worldview; toponymy; hydronims; onyms; zoonyms